The effectiveness of the six thinking hats strategy for teaching the curriculum and teaching methods course in developing creative thinking skills and achievement among students of the Faculty of Education at the University of Tikrit - Mohammed, Ahmed Jasim (مجلة الشرق الأوسط للعلوم التربوية والنفسية, 2024)
This study aims to determine the effectiveness of the six thinking hats teaching strategy and teaching methods in developing creative thinking skills, which include five skills (fluency, originality, flexibility, sensitivity to problems, elaboration or detail) and then propose a treatment plan. A semi-experimental method was used. The research sample was represented by third-year psychology students in the School of Education and divided into two groups. Each group included (15) male and female students, and the exploratory group included second-year students of the same major, a total of (30) students and one student. The six thinking hats strategy was used for teaching, and the psychology students in the control and control groups were tested before and after the measurement. The mean score of the experimental group students in the pre-test was (70.07) with a standard deviation of (4.65), while the overall mean score of the experimental group students was (112.67) and (112.67). The standard deviation is (5.84), and the (T) test showed a significant difference (T = -22.1), and the significance level is 0.05, which is statistically significant. The study also showed that the mean score of the students in the experimental group for the pre-test was (48.53) with a standard deviation of (6.52) and the (T-test showed a difference in favour of the post-test as compared to the pre-test. -The measurement of the experimental group emphasized the effectiveness of applying the six thinking hats strategy and its importance in university education.